Intracellular fate of Ureaplasma parvum entrapped by host cellular autophagy. Issue 3 (15th January 2017) - Nishiumi, Fumiko; Ogawa, Michinaga; Nakura, Yukiko; Hamada, Yusuke; Nakayama, Masahiro; Mitobe, Jiro; Hiraide, Atsushi; Sakai, Norio; Takeuchi, Makoto; Yoshimori, Tamotsu; Yanagihara, Itaru
Abstract : U. parvum was internalized into HeLa cells by endocytosis and entrapped by the autophagic machinery. However, autophagy was inadequate for the complete elimination. U. parvum also reached recycling endosome and exported from HeLa cells through exocytosis. Abstract: Genital mycoplasmas, including Ureaplasma spp., are among the smallest human pathogenic bacteria and are associated with preterm birth. Electron microscopic observation of U. parvum showed that these prokaryotes have a regular, spherical shape with a mean diameter of 146 nm. U. parvum was internalized into HeLa cells by clathrin‐mediated endocytosis and survived for at least 14 days around the perinuclear region. Intracellular U. parvum reached endosomes in HeLa cells labeled with EEA1, Rab7, and LAMP‐1 within 1 to 3 hr. After 3 hr of infection, U. parvum induced the cytosolic accumulation of galectin‐3 and was subsequently entrapped by the autophagy marker LC3. However, when using atg7 −/− MEF cells, autophagy was inadequate for the complete elimination of U. parvum in HeLa cells . U. parvum also colocalized with the recycling endosome marker Rab11. Furthermore, the exosomes purified from infected HeLa cell culture medium included U. parvum . In these purified exosomes ureaplasma lipoprotein multiple banded antigen, host cellular annexin A2, CD9, and CD63 were detected. This research has successfully shown that Ureaplasma spp. utilize the host cellular membrane compartments possibly to evade the host immune system.